Presumably you've proven exercise 6, that the Laplace transform of [tex]t^k f(t)[/tex] is [tex](-1)^k F^{(k)}(s)[/tex].
Let F(s) = 1/s, whose inverse Laplace transform is f(t) = 1. Differentiate F with respect to s :
[tex]F'(s) = -\dfrac1{s^2}[/tex]
By the claim from ex.6, this is the Laplace transform of t • f(t) = t.
Differentiate F again with respect to s :
[tex]F''(s) = \dfrac2{s^3}[/tex]
and this is the Laplace transform of t² • f(t) = t². And so on.
We can prove the general claim by induction. Assume it's true for n = k, that [tex]t^k \leftrightarrow \frac{k!}{s^{k+1}}[/tex]. Then using the result of ex.6, we have
[tex]F(s) = \dfrac{k!}{s^{k+1}} \implies F'(s) = -\dfrac{(k+1)!}{s^{k+2}} \leftrightarrow t^{k+1}[/tex]
QED